Importance of critical micelle concentration and surfactant's nature in emulsion polymerization of pyrrole monomer to yield superhydrophilic and underwater superoleophobic surface-engineered ceramics support membranes for oily wastewater treatment - Umair Baig; Abdul Waheed (Results in Engineering)
The development of promising membrane-based separations for treating tedious and complex oily wastewater streams is of utmost importance in recovering precious water. A facile and simple approach leading to promising membranes is always required for the sake of treating oily wastewater. This work has been focused on studying the effect of different surfactants on the emulsion polymerization of pyrrole monomer to yield superhydrophilic and underwater superoleophobic surface-engineered ceramics support membranes and their performance for the treatment of oily wastewater. Three surfactants namely sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), and Pluronic F127 were used during emulsion polymerization. All membranes showed excellent separation of surfactant-stabilized oil-in-water (O/W) emulsion coupled with good permeate flux. The separation efficiencies of the Ppy-SDS@Alumina, Ppy-CTAB@Alumina, and Pluronic F127@Alumina membranes were found to be >99 % for 100 ppm crude O/W emulsion. The permeate flux of the membranes was found to be 274.6, 1436, 950.7, and 1563 L m−2 h−1 for the Ppy-CTAB-1@Alumina, Ppy-SDS@Alumina, Ppy-CTAB@Alumina, and Pluronic F127@Alumina membranes at 1 bar, respectively. Among the different membranes, the Ppy-CTAB@Alumina was found to be the best-performing membrane owing to the higher concentration of CTAB than the critical micelle concentration (CMC). The higher concentration of CTAB than CMC resulted in a more uniform polymer compared to SDS and Pluronic F127. The Ppy-CTAB@Alumina membrane showed increased resistance to fouling coupled with enhanced flux recovery reaching 95 % compared to the other two membranes. This study established that critical micelle concentration is more crucial in controlling emulsion polymerization than the nature of the surfactants.